2022
DOI: 10.1186/s12884-022-05030-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of informational support from women’s social networks on antenatal care initiation: qualitative evidence from pregnant women in Uganda

Abstract: Background: Early and appropriate use of antenatal care services is critical for reducing maternal and neonatal mortality and morbidity. Yet most women in sub-Saharan Africa, including Uganda, do not seek antenatal care until later during pregnancy. This qualitative study explored pregnant women's reliance on social ties for information about initiation of antenatal care. Methods:We conducted semi-structured, in-depth interviews with 30 pregnant women seeking their first antenatal care visit at Kawempe Referra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In Uganda, almost all women (97.5%) seek prenatal care during pregnancy, but only 30% during the first trimester and only 60% have four or more visits [ 116 ]. A study in Rwanda showed that mothers were the group that had the most significant influence on the decision of pregnant women to seek care [ 117 ]. In Africa, mobile phones are displacing radio and television as a means of social communication [ 118 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Uganda, almost all women (97.5%) seek prenatal care during pregnancy, but only 30% during the first trimester and only 60% have four or more visits [ 116 ]. A study in Rwanda showed that mothers were the group that had the most significant influence on the decision of pregnant women to seek care [ 117 ]. In Africa, mobile phones are displacing radio and television as a means of social communication [ 118 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Uganda, almost all women (97.5%) seek Prenatal care during pregnancy, but only 30% during the first trimester and only 60% have four or more visits [118]. A study in Rwanda showed that mothers were the group that had the most significant influence on the decision of pregnant women to seek care [119]. In Africa, mobile phones are displacing radio and television as a means of social communication [120].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the World Health Organization (WHO) updated Focused Antenatal Care (FANC) model recommends at least 4 ANC visits for uncomplicated pregnancies, with the first visit beginning before 16 weeks of gestation [7]. However, studies show that the great majority of mothers in sub-Saharan Africa begin antenatal care far later than is recommended [8].…”
Section: Introduction Backgroundmentioning
confidence: 99%